2019
DOI: 10.1128/aac.02341-18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aerosolized Rifaximin versus Tobramycin for Treatment of Pseudomonas aeruginosa Pneumonia in Mice

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic bacterial pathogen that can cause chronic lung infections in patients with cystic fibrosis (CF). The current preferred treatment for CF lung infections includes inhaled tobramycin (TOB); however, studies suggest TOB cannot effectively inhibit biofilm formation. Using an NIH small compounds drug library approved for safe use in humans, we identified rifaximin (RFX), a semisynthetic, rifamycin family, nonsystemic antibiotic that inhibits alginate production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Following the exclusion of additional studies that focused on interventions or therapies other than small molecule antibiotics (monoclonal antibodies, bacteriophages, metal chelators, plant extracts, Lactobacillus , etc. ), 53 studies remained ( López-Rojas et al, 2011 ; Pachón-Ibáñez et al, 2011 ; Docobo-Pérez et al, 2012 ; Tang et al, 2012 ; Wang et al, 2012 ; Yamada et al, 2012 , 2013a , b ; He et al, 2013 ; Hirsch et al, 2013 ; Jacqueline et al, 2013 ; Louie et al, 2013 , 2015 ; Harada et al, 2014 ; Hengzhuang et al, 2014 ; Yokoyama et al, 2014 ; Bowers et al, 2015 ; Cheah et al, 2015 ; Berkhout et al, 2016 ; Brunetti et al, 2016 ; Cigana et al, 2016 ; Lepak and Andes, 2016 ; Mardirossian et al, 2016 ; McCaughey et al, 2016 ; Parra Millán et al, 2016 ; Thabit et al, 2016 ; Yang et al, 2016 ; Kaku et al, 2017a , b ; Li Y. T. et al, 2017 , Li Y. et al, 2017 ; Lin et al, 2017a , b , 2018 ; Oshima et al, 2017 ; Sakoulas et al, 2017 ; Zhou J. et al, 2017 , Zhou Y. F. et al, 2017 ; Avery et al, 2018 ; Chen et al, 2018 ; de Paula et al, 2018 ; Geller et al, 2018 ; Lou et al, 2018 ; Monogue et al, 2018 ; Kirby et al, 2019 ; Ku et al, 2019 ; Nakamura et al, 2019 ; Ren et al, 2019 ; Sanderink et al, 2019 ; Zhao et al, 2019 ; Johnson et al, 2020 ; Tan et al, 2020 ; Ma X. L. et al, 2020 ; Supplementary Table 2 ). Murine model variables were extracted from these articles to generate a data set for further analyses of experimental conditions.…”
Section: Literature Search Strategy Study Selection and Publication C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the exclusion of additional studies that focused on interventions or therapies other than small molecule antibiotics (monoclonal antibodies, bacteriophages, metal chelators, plant extracts, Lactobacillus , etc. ), 53 studies remained ( López-Rojas et al, 2011 ; Pachón-Ibáñez et al, 2011 ; Docobo-Pérez et al, 2012 ; Tang et al, 2012 ; Wang et al, 2012 ; Yamada et al, 2012 , 2013a , b ; He et al, 2013 ; Hirsch et al, 2013 ; Jacqueline et al, 2013 ; Louie et al, 2013 , 2015 ; Harada et al, 2014 ; Hengzhuang et al, 2014 ; Yokoyama et al, 2014 ; Bowers et al, 2015 ; Cheah et al, 2015 ; Berkhout et al, 2016 ; Brunetti et al, 2016 ; Cigana et al, 2016 ; Lepak and Andes, 2016 ; Mardirossian et al, 2016 ; McCaughey et al, 2016 ; Parra Millán et al, 2016 ; Thabit et al, 2016 ; Yang et al, 2016 ; Kaku et al, 2017a , b ; Li Y. T. et al, 2017 , Li Y. et al, 2017 ; Lin et al, 2017a , b , 2018 ; Oshima et al, 2017 ; Sakoulas et al, 2017 ; Zhou J. et al, 2017 , Zhou Y. F. et al, 2017 ; Avery et al, 2018 ; Chen et al, 2018 ; de Paula et al, 2018 ; Geller et al, 2018 ; Lou et al, 2018 ; Monogue et al, 2018 ; Kirby et al, 2019 ; Ku et al, 2019 ; Nakamura et al, 2019 ; Ren et al, 2019 ; Sanderink et al, 2019 ; Zhao et al, 2019 ; Johnson et al, 2020 ; Tan et al, 2020 ; Ma X. L. et al, 2020 ; Supplementary Table 2 ). Murine model variables were extracted from these articles to generate a data set for further analyses of experimental conditions.…”
Section: Literature Search Strategy Study Selection and Publication C...mentioning
confidence: 99%
“…We observed that the vast majority of the studies were carried out in female mice regardless of the bacteria used for infection ( Table 2 ). Interestingly, only one study used both female and male mice in separate experiments with different readouts ( Kirby et al, 2019 ; Table 2 ). Female C57BL/6J mice have been shown to be more susceptible to A. baumannii lung infection than their male counterparts ( Pires et al, 2020 ).…”
Section: Review Of Key Variables In Murine Bacterial Pneumonia Models...mentioning
confidence: 99%
“…Clinically, treatment of infectious diseases requires thorough bactericidal effect until the infectious inflammation is resolved [39,40]. Therefore, a repeated dose of antibiotics is often prescribed to maintain an adequate concentration of the drug at the site of infection [41][42][43]. Our repeated administration experiment showed that although single or two-time hinokitiol administration did not significantly lower the bacterial load 4 days after infection, repeating the procedure three times successfully decreased the bacterial load in the mouse pneumonia model.…”
Section: Discussionmentioning
confidence: 75%
“…In the bacteremia model, both FK20 and FdK attenuated the burden of PAO1 in spleens by 1.37 and 1.41 log and USA300 LAC burden in spleens by 1.90 and 1.86 log, respectively (Figure 5B,C). In mouse studies with conventional antibiotics, pneumonia models showed a 2.5-(P. aeruginosa, tobramycin) 45 and 1.5-log (MRSA, vancomycin) 46 decrease in CFUs, while sepsis models had a 3-log (P. aeruginosa, colistin, and MRSA, vancomycin) 46,47 decrease in CFUs. One important note is that the therapeutic dose of FK20 and FdK (10 mg/kg) was ∼5× higher than that of the FK20− Cy7.5 used for the live IVIS-based imaging.…”
Section: ■ Results and Discussionmentioning
confidence: 99%